An overview of the Portuguese wind power sector - Ferreira, Paula Varandas (2007)
In the following paper the present situation of the electricity production from Renewable energy Sources (RES) in Portugal is analysed, giving particular attention to the wind power sector due to its increasing importance. The evolution of the electricity system is presented along with the strategies for the sector, and future prospects for the RES. Although the high interest of private companies in the wind sector the administrative and grid barriers represent major obstacles to the wind power development. The problem of the wind intermittency and uncertainty is also discussed. The improvement of interconnection capacity and the increase of power reserve are identified as key requirements for ensuring the security of supply. A clear comprehension of all these aspects is fundamental to aim for an integrated multidimensional wind power planning.